Impact of COVID-19 pandemic on obesity among adults in Jordan - Rababah, Taha; Al-U'datt, Muhammad; Angor, Malak M.; Gammoh, Sana; Rababah, Rana; Magableh, Ghazi; Almajwal, Ali; AL-Rayyan, Yara; AL-Rayyan, Numan (Frontiers in Nutrition, 2023)
Abstract COVID-19 is a severe acute respiratory syndrome that mainly affects the human respiratory system. Unhealthy nutritional habits and obesity are expected as consequences of protective measures including quarantine. Obesity, in its growing prevalence, is a worldwide health issue associated with worsening health conditions. This is a cross-sectional study to assess the impact of the COVID-19 pandemic on obesity among Jordanian adults and across epidemiological statuses. Participants were randomly selected, and the survey was distributed on social media networking sites. A total of 672 subjects were surveyed and participated in the study between March and June 2021 via Google Form questionnaire. The results indicated that 74.4% of participants reported that they did not do any physical activity, and 43.5% changed their lifestyle and eating habits for the worse. During the COVID-19 pandemic, almost half of the participants reported an increase in hunger, consuming 3-4 meals/day, and consuming less than one liter of water/day. Additionally, more than half of the participants reported no change in fat, cereals, and protein consumption, 46.4 % had no change in fruit and vegetable consumption, and 50.6% increased their consumption of sweets. Our results showed a significant increase in the self-reported BMI categories during the COVID-19 pandemic for all ages (p< 0.001). Change in weight and BMI was significantly associated with marital status, education level, living place, family size, family working members, and working status. Participants across all epidemiological statuses displayed a statistically significant increase in BMI. This study was conducted to observe the impacts of the COVID-19 pandemic on health behaviors and obesity among Jordanian adults and across epidemiological statuses. We found that there were significant negative changes in the lifestyle (physical activity) and eating behaviors among Jordanians during the COVID-19 quarantine which in turn increased their body weight and changed the obesity rate.